Reducing options of ammonia volatilization and improving nitrogen use efficiency via organic and inorganic amendments in wheat (Triticum aestivum L.) - Pooja L. Ramalingappa; Manoj Shrivastava; Shiva Dhar; Kalikinkar Bandyopadhyay; Shiv Prasad; Sapna Langyan; Ritu Tomer; Ashish Khandelwal; Sibananda Darjee; Renu Singh (PeerJ, 2023)
Background This study investigates the effect of organic and inorganic supplements on the reduction of ammonia (NH3) volatilization, improvement in nitrogen use efficiency (NUE), and wheat yield. Methods A field experiment was conducted following a randomized block design with 10 treatments i.e., T1-without nitrogen (control), T2-recommended dose of nitrogen (RDN), T3-(N-(n-butyl) thiophosphoric triamide) (NBPT @ 0.5% w/w of RDN), T4-hydroquinone (HQ @ 0.3% w/w of RDN), T5-calcium carbide (CaC2 @ 1% w/w of RDN), T6-vesicular arbuscular mycorrhiza (VAM @ 10 kg ha−1), T7-(azotobacter @ 50 g kg−1 seeds), T8-(garlic powder @ 0.8% w/w of RDN), T9-(linseed oil @ 0.06% w/w of RDN), T10-(pongamia oil @ 0.06% w/w of RDN). Results The highest NH3 volatilization losses were observed in T2 at about 20.4 kg ha−1 per season. Significant reduction in NH3 volatilization losses were observed in T3 by 40%, T4 by 27%, and T8 by 17% when compared to the control treatment. Soil urease activity was found to be decreased in plots receiving amendments, T3, T4, and T5. The highest grain yield was observed in the T7 treated plot with 5.09 t ha−1, and straw yield of 9.44 t ha−1 in T4. Conclusion The shifting towards organic amendments is a feasible option to reduce NH3 volatilization from wheat cultivation and improves NUE.